The alteration of spontaneous low frequency oscillations caused by acute electromagnetic fields exposure - Lv, Bin; Chen, Zhiye; Wu, Tongning; Shao, Qing; Yan, Duo; Ma, Lin; Lu, Ke; Xie, Yi (Clinical neurophysiology, 2014)
•The resting state fMRI was applied to investigate the Long Term Evolution (LTE) radiofrequency electromagnetic field (RF-EMF) exposure influence on spontaneous brain activity.•A controlled LTE RF-EMF exposure environment was designed, and the amplitude of low frequency fluctuation (ALFF) and fractional ALFF (fALFF) approaches were selected to analyze the resting state fMRI signals.•We found the spontaneous low frequency oscillations in brain were altered by the acute LTE RF-EMF exposure. The motivation of this study is to evaluate the possible alteration of regional resting state brain activity induced by the acute radiofrequency electromagnetic field (RF-EMF) exposure (30min) of Long Term Evolution (LTE) signal. We designed a controllable near-field LTE RF-EMF exposure environment. Eighteen subjects participated in a double-blind, crossover, randomized and counterbalanced experiment including two sessions (real and sham exposure). The radiation source was close to the right ear. Then the resting state fMRI signals of human brain were collected before and after the exposure in both sessions. We measured the amplitude of low frequency fluctuation (ALFF) and fractional ALFF (fALFF) to characterize the spontaneous brain activity. We found the decreased ALFF value around in left superior temporal gyrus, left middle temporal gyrus, right superior temporal gyrus, right medial frontal gyrus and right paracentral lobule after the real exposure. And the decreased fALFF value was also detected in right medial frontal gyrus and right paracentral lobule. The study provided the evidences that 30min LTE RF-EMF exposure modulated the spontaneous low frequency fluctuations in some brain regions. With resting state fMRI, we found the alteration of spontaneous low frequency fluctuations induced by the acute LTE RF-EMF exposure.